The Phraseocheme "Was Für + Sub1-4!" in the System of German Language (Proceedings of Southern Federal University. Philology, 2017)
Anastasia D. Melnik (Rostov-on-Don, Russian Federation)This article is devoted to the description of the phraseological syntax of the modern German language «Was für + Sub1-4!». The relevance of the study is due to the insufficient study of this subject, but also to its high relevance for the practice of communication. The following methods were used in the research: descriptive, method of component analysis of the semantic structure of the sentence, syntactic modeling, phraseological analysis, transformation method, and also the method of etymological, contextual and discursive analysis.The phrase «Was für + Sub1-4!» is described in the structural, semantic, etymological, paradigmatic, syntagmatic, stylistic, phraseological and functional aspects. The article substantiates the phraseological status of the given phrase-scheme and its belonging to the phraseological subsystem of the language. It is established that the phraseological scheme has two obligatory components (unchangeable and variable), characterized by signs of reproducibility, structural and semantic stability and integrity, idiomatic and expressive, possesses an unchangeable structure serving as a model for constructing similar propositions. In general, the phraseology «Was für + Sub1-4!» is quite frequent in the practice of communication, which is due to its systemic and functional characteristics. Its use in colloquial speech increases the effectiveness of the communication process, gives it a relaxed character.Key words: syntactic phraseology; syntactic phraseological unit; phraseosyntactic scheme; German.DOI 10.23683/1995-0640-2017-3-66-74